A Weighted Solution Concept under Replicated Behavior - Yu-Hsien Liao (Mathematics, 2022)
In the framework of traditional transferable-utility (TU) models, the participants are either entirely involved or not involved in interactive processes with some other participants. Based on the distribution notion of the equal allocation of non-separable costs (EANSC), all participants first receive their marginal contributions and further distribute the remaining utilities equally. In real-world situations, however, participants might adopt different participation levels to participate. Moreover, participants might represent coalitions of different scales; participants might have corresponding influences under different situations. Thus, in this paper we propose a generalization of the EANSC by considering weights and replicated notions under conditions of multi-choice behavior simultaneously. In order to dissect the mathematical accuracy and the applied rationality of this expanded EANSC, a specific reduction is introduced to present an axiomatic result and a dynamic process, respectively.